Intraoperative intact parathyroid hormone monitoring and frozen section diagnosis are essential for successful parathyroidectomy in secondary hyperparathyroidism - Hiramitsu, Takahisa; Hasegawa, Yuki; Futamura, Kenta; Okada, Manabu; Goto, Norihiko; Narumi, Shunji; Watarai, Yoshihiko; Tominaga, Yoshihiro; Ichimori, Toshihiro (Frontiers in Medicine, 2022)
Background Total parathyroidectomy (PTx) is often performed to treat secondary hyperparathyroidism (SHPT). Successful PTx is essential to prevent recurrent and persistent SHPT because remnant parathyroid glands (PTGs) in the neck can be stimulated and may secrete excessive parathyroid hormone (PTH) in end-stage renal disease. However, to date, few studies have investigated factors contributing to successful PTx before the completion of surgery. Materials and methods Between August 2010 and February 2020, 344 patients underwent total PTx, transcervical thymectomy, and forearm autograft for SHPT at our institute. Factors contributing to successful PTx before the completion of surgery were investigated. Preoperative imaging diagnoses, including computed tomography, ultrasonography, technetium-99m methoxyisobutylisonitrile (99mTc-MIBI) scintigraphy, intraoperative intact PTH (IOIPTH) monitoring, and frozen section histologic diagnosis, were performed. Successful PTx was defined as intact PTH level < 60 pg/mL on postoperative day 1. A sufficient decrease in IOIPTH level was defined as > 70% decrease in intact PTH levels measured 10 min after total PTx and transcervical thymectomy compared to intact PTH levels measured before skin incision. Logistic regression analysis was conducted to investigate factors contributing to PTx success. Results Univariate analysis showed that the number of all PTGs identified preoperatively by imaging modalities and the specimens submitted for frozen section diagnosis, which surgeon presumed to be PTGs, were not significant factors contributing to successful PTx. However, multivariate analysis revealed that the number of PTGs identified by frozen section diagnosis (P < 0.001, odds ratio [OR] 4.356, 95% confidence interval [CI] 2.499–7.592) and sufficient decrease in IOIPTH levels (P = 0.001, OR 7.847, 95% CI 2.443–25.204) significantly contributed to successful PTx. Conclusion Sufficient intact PTH level decrease observed on IOIPTH monitoring and the number of PTGs identified by frozen section diagnosis contributed to successful PTx for SHPT. IOIPTH monitoring and frozen section diagnosis are essential for achieving successful PTx for SHPT.